P0602CLINICAL PATTERN, RENAL RECOVERY AND PATIENT OUTCOMES AFTER ACUTE KIDNEY INJURY IN ADULTS IN AN EMERGING COUNTRY. (6th June 2020) - Subbiah, Arunkumar; Agarwal, Sanjay Kumar
Abstract: Background and Aims Acute Kidney Injury (AKI) is an important determinant of outcome in hospitalized patients. Further, there is a risk for development of Chronic Kidney Disease (CKD) in the future. Though the long-term impact of AKI has been studied in developed countries, there is a paucity of data in this area from the Indian subcontinent. This single-centre study aimed to assess the pattern, clinical spectrum, short-term and long-term outcomes of AKI. Method In this prospective observational cohort study, detailed demographic and clinical data at presentation, during hospital stay and follow-up at 1, 3, 6 and 12 months after discharge were obtained prospectively for a cohort of patients with AKI. Both community (CAAKI) and hospital acquired AKI (HAAKI) were included. Patient with pre-existing CKD were excluded. Outcome variables examined were in-hospital mortality, renal function at discharge and on follow-up after discharge from hospital. Results In our study cohort with 476 patients, majority of the cases were CAAKI (395, 83%). The mean age at presentation was 44.8 ± 18.7 years. Medical causes (84%) contributed to the majority of AKI while the remaining were due to surgical (10%) and obstetrical (6%) causes. Sepsis (176/476; 36.9%) was the most common cause of AKI. The most common source for sepsis was respiratory (41%) followed by urological source (18.7%). The in-hospital mortality rate for patients with AKI was 38%. Age >60 years (HR = 1.51; 95% CI, 1.11 – 2.07), oliguria (HR = 1.48; 95% CI, 1.05 – 2.10), need for ventilator (HR = 2.45; 95% CI, 1.36 – 4.41) and/or inotropes (HR = 14.4; 95% CI, 6.28 – 33.05) were predictors of mortality. At discharge, 146 (30.7%) patients had complete renal recovery, while 149 (31.3%) had partial renal recovery. Oliguria (p < 0.001), hypoalbuminemia (p = 0.001) and need for renal replacement therapy (RRT) (p = 0.01) were significantly associated with partial recovery. Of the 295 patients on follow-up at discharge, 211 (71.5%) patients had normal renal function, 4 (1.4%) died and 33 (11.2%) were lost to follow up; 47(15.9%) patients developed CKD of which 6 (2%) were dialysis dependent. Elderly patients, higher AKIN stage with oliguria and those requiring RRT were more likely to develop CKD. Among these, the need for in-hospital RRT was the single most important factor predicting the risk of CKD (OR 1.77, 95% CI, 1.12-2.78). Conclusion In conclusion, our data shows that AKI in hospitalized patients still has high mortality in emerging countries like India. Though a fairly good percentage of cases recovered, there is a definite risk of CKD development, especially in patients who required RRT during hospitalization.